Feeding the world in 2050: Trade‐offs, synergies and tough choices for the livestock sector - Smith, Jimmy W.; Tarawali, Shirley A.; Grace, Delia; Sones, Keith R. (2013)
Feeding the World in 2050 is a major challenge at the forefront of the global development agenda. The importance of agriculture in addressing this challenge has re-emerged in recent years as food security issues are considered in a more holistic manner. The role of livestock as part of the solution is, however, often not considered. This article presents a brief overview of the global food security challenge, and considers the increased focus on holistic food systems. It contends that animal agriculture is relevant to this complex, multifaceted and dynamic global challenge. However, if livestock-based solutions are to become a reality, a number of partial truths and trade-offs often associated with livestock and food need to be addressed. The role of livestock systems in future food security is considered in relation to different potential development trajectories of the sector, highlighting opportunities to ensure that livestock’s contribution to global food security is a positive one, which also addresses concerns of environment, equity and human health.